Testing for spatial market integration: evidence for Colombia using a pairwise approach (2017)
We examine the extent of spatial market integration in Colombia using consumer price index data for 153 consumer goods in 13 cities. An econometric analysis of the time-series properties of all the possible city price differentials reveals that market integration tends to occur more frequently in unprocessed food products, as opposed to processed foods, other traded and nontraded products. The results also support the view that, except for nontraded products, the speed at which prices adjust to the long-run equilibrium is slower for cities that are farther apart. © 2017 International Association of Agricultural Economists